Effect of stress management based on cognitive–behavioural therapy on nurses as a universal prevention in the workplace: a systematic review and meta-analysis protocol. Issue 9 (19th September 2022) - Kuribayashi, Kazuto; Takano, Ayumi; Inagaki, Akiko; Imamura, Kotaro; Kawakami, Norito
Abstract : Introduction: The mental health status of nurses affects not only their well-being but also the organisational outcomes and the quality of patient care. Hence, stress management strategies are critical as a universal prevention measure that address an entire population and are not directed at a specific risk group to maintain nurses' mental health in the workplace. No systematic review or meta-analysis has been conducted to evaluate the effect of cognitive–behavioural therapy (CBT) that specifically focuses on universal prevention. Therefore, the aim of this study is to examine the effectiveness that is reported in published randomised controlled trial (RCT) studies. Methods and analysis: This systematic review and meta-analysis will analyse published studies selected from electronic databases (ie, Cochrane Central Register of Controlled Trials, PubMed, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, PsycARTICLES, Web of Science and the Japan Medical Abstracts Society). The inclusion criteria for studies are that they (1) were conducted to assess the effect of CBT on the mental health of nurses as a universal prevention, (2) used an RCT design and (3) provided sufficient results (sample sizes, means and SD) to estimate the pooled effect sizes with 95% CIs. Studies will be excluded if they only targeted nurses who had been screened as being at high risk in terms of their mental health and indicated that they required the prevention. The methodological quality of the included studies will be assessed using the Cochrane Collaboration's risk of bias tool. Ethics and dissemination: Ethical approval is not required because this study is based on information obtained from previous studies. The results and findings of this study will be submitted for publication in a peer-reviewed international scientific journal. Results from this study will be helpful when implementing CBT strategies for nurses as a universal preventative measure in the workplace and for managing stress-related outcomes. PROSPERO registration number: CRD42020152837.